Circumstantial Adjunct used in the Novella “A Reason to Rain” by Donna M. Young - Bunga Rifka Bintara (English Teaching and Linguistics Journal (ETLiJ), 2022)
This research aims to describe the different types of circumstantial adjuncts and the primary forms of circumstantial adjuncts identified in Donna M. Young's novella